Application of Video-Assisted Symbolic Modeling Techniques to Reduce Bullying Behavior - Reisa Amalia; Hesty Nurrahmi; Randi Saputra; Adiansyah Adiansyah; Nanda Alfan Kurniawan (Jurnal Counseling Care, 2026)
This study aims to analyze the effect of providing group guidance services using symbolic modeling techniques assisted by video media on reducing bullying behavior. This study uses a quantitative approach with a pre-experimental design, one group pretest-posttest design. The sample collection technique uses purposive sampling. The sample of this study consisted of 8 students of grade VIII of junior high school. Data collection techniques used observation, questionnaires, and documentation. Data analysis was carried out through validity tests, reliability, descriptive statistics, normality, and paired sample t-tests. The results showed that the average score of bullying behavior before being provided with services was 51.25, while after being provided with services decreased to 33.25. The results of the paired sample t-test showed a calculated t value of 12.961 with a significance value of 0.001 (<0.05). The results showed a decrease in bullying behavior after students participated in group guidance services using symbolic modeling techniques assisted by video media. In-depth testing using replication of a larger sample size with a quasi-experimental design is needed in future studies to determine the effectiveness of services in cases of bullying in junior high school students in the future.